Research in computational molecular biology : 16th Annual International Conference, RECOMB 2012, Barcelona, Spain, April 21-24, 2012. Proceedings - Chor, Benny (Lecture Notes in Computer Science, 2012)
This book constitutes the refereed proceedings of the 16th Annual International Conference on Research in Computational Molecular Biology, RECOMB 2012, held in Barcelona, Spain, in April 2012. The 31 revised full papers presented together with 5 keynote lectures were carefully reviewed and selected from 200 submissions. The papers feature current research in all areas of computational molecular biology, including: molecular sequence analysis; recognition of genes and regulatory elements; molecular evolution; protein structure; structural genomics; analysis of gene expression; biological networks; sequencing and genotyping technologies; drug design; probabilistic and combinatorial algorithms; systems biology; computational proteomics; structural and functional genomics; information systems for computational biology and imaging.